Analysis Model of the Impact of the Covid-19 Pandemic on the Profitability of SMEs - Ardian Widiarto; Lardin Korawijayanti; Arum Febriyanti Ciptaningtias; Tutik Dwi Karyanti (Ilomata International Journal of Management, 2022)
This study aims to and analyze the extent of the influence of the covid-19 pandemic on the Profitability of the Water Hyacinth Craft Cluster SMEs "Klinting" in Semarang Regency. The research method used is a hypothetical empirical method that is used to test the difference between the ability to earn profits (Profitability) of the Water hyacinth Handicraft Klater SMES "Klinting" before and during the Covid-19 pandemic. Profitability of Water Hyacinth Craft Cluster "Klinting" Kab. Semarang in 2019 is 26% and in 2020 is 21%. The results of the different test using the paired sample t test resulted in a value of t = 2.763 with a 2-tailed significance of 0.018, less than 0.05, so Ho was rejected and Hi was accepted. So it was concluded that there were significant differences in the Klinting Cluster Encenggondok SMEs in earning profits before and during the Covid-19 pandemic.